(untitled) (Jurnal Bahasa, 2006)
This study is designed to compare language learning strategies used by good and poor learners to improve the reading and writing skills of bahasa Melayu in the classroom. A total of four good learners and four poor learners were chosen by a group of bahasa Melayu teachers. This "multicase single site" case study uses interview protocol to identifr strategies for improving reading and writing skills. The inter-view data were analysed using Cohen Kappa to determine the main themes emergingfrom transcripts obtained. Findings showed that good learners used more language learning strategies than poor learners in the classroom for both language skills. In addition, there were some differences of language learning strategies used by both group of stu-dents in both language skills.